2011
DOI: 10.1186/1475-2867-11-44
|View full text |Cite
|
Sign up to set email alerts
|

Multi-tyrosine kinase inhibitors in preclinical studies for pediatric CNS AT/RT: Evidence for synergy with Topoisomerase-I inhibition

Abstract: BackgroundCurrently, Atypical Teratoid Rhabdoid Tumor (AT/RT) constitutes one of the most difficult to treat malignancies in pediatrics. Hence, new knowledge of potential targets for therapeutics and the development of novel treatment approaches are urgently needed. We have evaluated the presence of cytokine pathways and the effects of two clinically available multi-tyrosine kinase inhibitors for cytotoxicity, target modulation and drug combinability against AT/RT cell lines.ResultsAT/RT cell lines expressed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…The sorafenib-irinotecan combination is not toxic in xenografted mice, and some clinical trials have reported that they can be associated for the treatment of KRAS-mutated tumors (29,36). Moreover, a not yet published phase II trial (42), carried out in patients with irinotecan-resistant and KRAS-mutated CRCs, shows hopeful results.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The sorafenib-irinotecan combination is not toxic in xenografted mice, and some clinical trials have reported that they can be associated for the treatment of KRAS-mutated tumors (29,36). Moreover, a not yet published phase II trial (42), carried out in patients with irinotecan-resistant and KRAS-mutated CRCs, shows hopeful results.…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, irinotecan failure can also be related to activation of NF-kB and inhibition of the apoptotic cascade. Jayanthan and colleagues (36) have shown that, in cell lines derived from atypical teratoid rhabdoid tumors of the central nervous system, sorafenib could interfere with irinotecan-mediated NF-kB activation by retaining NF-kB in the cytoplasm and, therefore, preventing induction of antiapoptotic genes. Another hypothesis is that sorafenib could modify metabolism of irinotecan.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib has been reported to demonstrate significant activity against several receptor tyrosine kinases involved in neovascularization and tumor progression, including VEGFR-2, VEGFR-3, platelet-derived growth factor receptor beta, Flt-3, and c-KIT [23]. The off-targets of Sorafenib that were retrieved using MEDIT SA MED-SuMo and were validated through literature are given in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…В исследовании, проведенном B. Koos et al, сообщалось, что иматиниб, мульти-TKI первого поколения, ингибирует рост клеток через c-Abl в рабдоидных линиях G401 и A204 [2,57]. Аналогичным образом, исследования in vitro клеточных линий АТРО идентифицировали двойной сосудистый эндотелиальный фактор роста/ингибиторы митоген-активируемой протеинкиназы 1 (VEGF/ MEK) с двойной специфичностью сорафениб и сунитиниб в качестве перспективных агентов при тестировании отдельно или в комбинации с иринотеканом, ингибитором топоизомеразы I [2,58,59]. В исследовании, проведенном J. Torchia et al, показано, что мульти-TKI второго поколения, нилотиниб и дазатиниб, снижали клеточную пролиферацию при наномолярных концентрациях, особенно в группе 2 АТРО, путем ингибирования бета-рецептора тромбоцитарного фактора роста (PDGFRβ), который дифференциально эпигенетически регулируется в разных подгруппах [2,6].…”
Section: будущие направленияunclassified